Winner of the 2006/2007 RIWA Award - Editorial Team (Evidence Based Library and Information Practice, 2007)
It is with great pleasure that the Research in the Workplace Award (RIWA)* assessment panel announces the winning proposal in 2006/2007 to be for a multi-site randomised controlled trial to determine the impact of providing a virtual reference service (Access Specialist Knowledge - ASK) to the local Primary Care and Mental Health Trusts within the UK National Health Service. The project will be led by Rachel Southon, Royal Surrey County Hospitals NHS Trust, in collaboration with Vicki Veness, also of Royal Surrey County Hospitals NHS Trust and John Loy, Avon & Wiltshire Mental Health Partnership NHS Trust. The project will commence in April 2007 and the assessment panel believes it will yield measurable outcomes and provide an evidence base for developing services to primary care. The project is due for completion by March 2008 and will be followed by a comprehensive programme of dissemination. A copy of the winning proposal can be accessed via the RIWA* web site at: http://ifmh.org.uk/RIWA.html. The proposal was considered to be well planned and an exemplary model of a proposal in terms of identifying an important question and an appropriate methodology with which to address it. RIWA* is a biennial award and details of projects which have previously been funded, together with news of future awards, can be found on the RIWA* web site at: http://ifmh.org.uk/RIWA.html. RIWA 2006/2007 is managed by IFM Healthcare and is sponsored by National Library for Health CPD Forum, IFM Healthcare, the Health Libraries Group, the University Medical School Librarians Group, and the University Health Sciences Libraries and Libraries for Nursing.